The Use of Diorama Learning Media Towards Learning Motivation of Students in Class X IPS 2 - Fitri, Imelda Setya; Zulfan, Zulfan; Rosita, Dara (Universitas Syiah Kuala, 2022)
The research entitled The Use of Diorama Learning Media on Student Motivation in Class X Social Sciences 2 SMA Negeri 1 Rundeng District